Effects of feeding ractopamine hcl (paylean) for various durations on late-finishing pig performance and carcass characteristics - Potter, M. L.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 627 pigs (241.5 lb) were used in a 21-d finishing trial to evaluate the effects of feeding ractopamine HCl (RAC; Paylean, Elanco Animal Health, Greenfield, IN) for different durations on growth performance and carcass characteristics. On d 0, pens of pigs containing both barrows and gilts in approximately equal numbers were blocked by average BW and randomly allotted to 1 of 3 dietary treatments (8 pens per treatment) with average initial weight balanced across treatments. Dietary treatments were feeding a control diet without RAC and feeding a diet containing 4.5 g/ton RAC for the last 14 or 21 d prior to marketing. Pens of pigs were weighed and feed intake was collected on d 0, 7, and 21 to calculate ADG, ADFI, and F/G. Carcass data were collected from the 4 heaviest pigs per pen marketed on d 7 and from all pigs marketed on d 21. Pigs fed RAC starting on d 0 gained faster (P = 0.01) and consumed less feed (P = 0.01) from d 0 to 7 than control pigs and pigs not yet fed RAC. From d 7 to 21, pigs started on RAC at d 7 had improved (P ≤ 0.04) ADG and F/G compared with control pigs and pigs that remained on RAC. There was no difference (P = 0.14) in overall ADG between the treatment groups; however, ADFI was lower (P < 0.01) and F/G improved (P < 0.01) for pigs fed RAC, regardless of duration, compared with control pigs. There were no differences (P ≥ 0.32) in overall live weight or HCW at market in this trial. Compared with control pigs, pigs fed RAC for 21 d had reduced (P < 0.01) backfat depth, increased (P = 0.01) loin depth, and improved (P < 0.01) percentage lean. Pigs fed RAC for 14 d had intermediate responses to these 2 treatments for loin and backfat depth but had a higher percentage lean than control pigs. These data demonstrate that feeding RAC to pigs for 14 d reduced ADFI, improved F/G, and improved percentage lean compared with control pigs. Feeding RAC for an additional 7 d did not influence overall ADFI or F/G compared with feeding RAC for 14 d total but further improved percentage lean compared with feeding RAC for 14 d. Pigs fed RAC for 21 d had decreased backfat and increased loin depth compared with control pigs. This study demonstrates that for heavyweight pigs, F/G and ADFI responses are achieved with either duration of RAC feeding, but the magnitude of the carcass response to feeding RAC appears to be duration dependent.
Keywords: Carcass; Growth; Paylean; Ractopamine; Swine